A self-powered 3D DNA walker with programmability and signal-amplification for illuminating microRNA in living cells. Issue 14 (23rd January 2020) - Yang, Xue-Jiao; Cui, Mei-Rong; Li, Xiang-Ling; Chen, Hong-Yuan; Xu, Jing-Juan
Abstract : We construct a target-triggered, self-powered 3D DNA walker for achieving intracellular signal amplification and sensitive imaging analysis of microRNAs. Abstract : Based on the structural programmability and spatial addressability of DNA nanodevices, a target-triggered, enzyme-free 3D DNA walker, comprising of hairpin DNA assembled gold nanoparticles with a local catalytic hairpin assembly reaction, was developed for the highly sensitive detection of intracellular tumor-associated microRNAs.